Influence of Three Extraction Methods on the Physicochemical Properties of Kefirans Isolated from Three Types of Animal Milk - Chiara La Torre; Alessia Fazio; Paolino Caputo; Antonio Tursi; Patrizia Formoso; Erika Cione (Foods, 2022)
Kefiran is a heteropolysaccharide biopolymer usually extracted from kefir grains cultured in cow milk. Due to the lack of information on exopolysaccharides from other types of animal milk, in the present study, cow, buffalo and goat milks were used as raw materials for fermentation. The kefiran extractions from kefir grains were carried out with cold water (method I), hot water (method II) and mild heated water-ultrasound (method III), and then the recovery yield and the physicochemical properties of the kefirans were evaluated to establish the influence of both the extraction conditions and the type of milk. The highest yield was recorded for the cow kefiran using method III (4.79%). The recoveries of goat and buffalo kefirans with methods II and III were similar (2.75–2.81%). Method I had the lowest yields (0.15–0.48%). The physicochemical characteristics were studied with Fourier Transform-Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), and Differential Scanning Calorimetry (DSC). Fourier-transform infrared spectroscopy showed the same qualitative profile for all the samples, regardless of the method and the type of milk, confirming that the extraction methods did not affect the chemical structure of the kefirans. Otherwise, the thermal and morphological features of the samples showed differences according to both the type of the milk and the extraction method. The kefiran samples were very thermally stable, having a temperature of degradation (Td) in the range from 264 to 354 °C. The resulting morphological and thermal differences could lead to different practical applications of kefirans in the fields of nutrition and pharmacology.